2019
DOI: 10.1111/pai.13119
|View full text |Cite
|
Sign up to set email alerts
|

Serum chitinase‐like protein YKL‐40 is linked to small airway function in children with asthmatic symptoms

Abstract: Background: Lung function impairment among asthmatic children begins in early life, and biomarkers for identifying this impairment are needed. The chitinase-like protein YKL-40 has been associated with asthma and lung function in adults, but studies in children have yielded conflicting results. We evaluated the potential of YKL-40 and other systemic biomarkers for identifying lung function deficits in children with asthmatic symptoms. Methods:We determined the levels of serum YKL-40, periostin, and high-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Thus, it is somewhat surprising that, in contrast to the findings in the OVA and HDM models described above, our experiment revealed a contrasting, protective/beneficial role for BRP-39 during fungal asthma. YKL-40 generally correlates with worse disease in human asthma (15,47,52,53). Indeed, we show that YKL-40 levels were elevated in fungal-sensitized asthmatics (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, it is somewhat surprising that, in contrast to the findings in the OVA and HDM models described above, our experiment revealed a contrasting, protective/beneficial role for BRP-39 during fungal asthma. YKL-40 generally correlates with worse disease in human asthma (15,47,52,53). Indeed, we show that YKL-40 levels were elevated in fungal-sensitized asthmatics (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…Similarly, Cho et al 20 found significantly higher periostin levels in children with positive exercise and mannitol tests when compared to children with asthma and negative results. Recently, the findings of Knihtilä et al 21 have demonstrated a significant correlation between serum periostin levels, airway hyper‐reactivity, and bronchodilator responsiveness in 49 children with asthmatic symptoms. In our study, we found a significant and independent correlation between asthma severity and serum periostin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [29] elegantly demonstrated in vitro that the chitinase-like molecule, Chi3l1, binds to the IL-13-receptor α2 and mediates biological responses, including the regulation of cellular apoptosis, oxidative tissue injury, and airway inflammation, thus linking this molecule with Th2-mediated allergic immune responses. Accordingly, serum levels of the chitinase-like protein YKL-40 showed significant correlations with the baseline lung function and were increased in children with a significant response in either the exercise challenge or the bronchodilator test [30]. Consequently, strategies to inhibit the induction of airway inflammation by blocking of chitinases would include attempts to obstruct upstream IL-13 production.…”
Section: Discussion/conclusionmentioning
confidence: 99%